2013
DOI: 10.5402/2013/410814
|View full text |Cite
|
Sign up to set email alerts
|

Shifts of Bacterioplankton Metabolic Profiles along the Salinity Gradient in a Subtropical Estuary

Abstract: Understanding the biodegradation potential of river bacterioplankton communities is crucial for watershed management. We investigated the shifts in bacterioplankton metabolic profiles along the salinity gradient of the Caloosahatchee River Estuary, Florida. The carbon source utilization patterns of river bacterioplankton communities were determined by using Biolog EcoPlates. The number of utilized substrates was generally high in the upstream freshwater dominated zone and low in the downstream zone, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
(52 reference statements)
1
6
0
Order By: Relevance
“…The overall CLPPs showed that the metabolic diversity was significantly enhanced from the summer (when ambient and water temperatures were the highest) to fall season, but it dropped rapidly in the winter (when ambient and water temperatures were the lowest). Similar results were found by Urakawa et al [ 49 ] who reported that bacterioplankton assemblages in the summer and fall showed more versatile substrate utilization patterns than winter and spring communities.…”
Section: Discussionsupporting
confidence: 90%
“…The overall CLPPs showed that the metabolic diversity was significantly enhanced from the summer (when ambient and water temperatures were the highest) to fall season, but it dropped rapidly in the winter (when ambient and water temperatures were the lowest). Similar results were found by Urakawa et al [ 49 ] who reported that bacterioplankton assemblages in the summer and fall showed more versatile substrate utilization patterns than winter and spring communities.…”
Section: Discussionsupporting
confidence: 90%
“…More specifically, after grouping every carbon source by chemical category, amino acids, carbohydrates and phenolic substances were highly consumed by BCs associated with N 2 - cyanobacteria ( Figure 3A ). Similarly, the NUI ( Urakawa et al, 2013 ) was significantly higher for BCs associated with N 2 - cyanobacteria than for those associated with N 2 + cyanobacteria (ANOVA analysis: df = 1, F -value = 289.5, p = 9.3 10 -14 ) ( Figure 3B ). Overall, among the different characteristics of the cyanobacterial strains (N 2 fixation, culture medium, date of isolation, genus and putative toxicity), only N 2 fixation/culture medium and the interactions among cyanobacterial strain, genus and N 2 fixation/culture medium had significant effects on carbon and nitrogen metabolic activities [ANOVA analyses using best models given by AIC analyses (∼Fixation + Fixation:Strain:Genus), df = 1 and F -value > 126.1 for N 2 fixation; df = 13 and F -value < 18.1 for Fixation:Strain:Genus, p < 0.001].…”
Section: Resultsmentioning
confidence: 91%
“…4b). Urakawa et al (2013) demonstrated that the detected variability among the environmental samples was not due to technical errors or poor reproducibility of CLPP methods, but rather by the community-level heterogeneity in the analyzed microbial samples. Thus, our observation indicates that toxic substances (such as pharmaceuticals) might be present in WWTP e uents, and these may have inhibited bacterial diversity at WWD sites compared to other sites in the fall (Nega et al 2019).…”
Section: Spatial and Seasonal Variations In Microbial Biomassmentioning
confidence: 94%